2018
DOI: 10.1115/1.4039643
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection and Surface Radiation in a Heated Wall, C-Shaped Fracture

Abstract: The present study considers the coupled natural convection and surface radiation process through an open fracture of a solid wall facing a reservoir containing isothermal quiescent fluid (air). The fracture is modeled as a regular, C-shape path through the wall, with the vertical surface being heated and the horizontal ones adiabatic. The solid center section of the fracture is thermally participant inasmuch it can be heated or cooled by the natural convection process and by the radiation effect from the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…There is a barrier with thermal conductivity within the cavity and, thus, they found that the ratio of thermal conductivity and block size were good controllers for heat transfer. Lugarimi et al [43] studied the natural and turbulent convection heat by means of the FVM. Inside the cavity, there was a square barrier.…”
Section: [ 888 ]mentioning
confidence: 99%
“…There is a barrier with thermal conductivity within the cavity and, thus, they found that the ratio of thermal conductivity and block size were good controllers for heat transfer. Lugarimi et al [43] studied the natural and turbulent convection heat by means of the FVM. Inside the cavity, there was a square barrier.…”
Section: [ 888 ]mentioning
confidence: 99%
“…Kwon et al (2018) presented an analytic approach to thermal optimization of horizontally oriented radial plate-fin heat sinks in natural convection. Lugarini et al (2018) studied natural convection and surface radiation in a heated wall with the C-shaped fracture. The above research works show the importance of natural convection and surface radiation heat transfer in the practical applications like the electronic cooling.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…Bangian-Tabrizi and Jaluria (2018) proposed an optimization strategy for the inverse solution of a convection heat transfer problem. Lugarini et al (2018) studied natural convection and surface radiation in a heated wall with the Cshaped fracture. Miroshnichenko and Sheremet (2018) studied the turbulent natural convection combined with thermal surface radiation inside an inclined cavity having local heater.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%